Traceability of bovine meat and bone meal in eggs from laying hens fed with alternative ingredients - Denadai, Juliana Célia (2009)
The objective of this work was to detect traces of the bovine meat and bones meal in eggs of laying hens fed on commercial diets including alternative plant ingredients and yeast. The bovine meal detection was performed through carbon and nitrogen stable isotope technique. Three hundred eighty-four laying hens were randomly distributed in eight treatments. Treatments consisted of one control diet – a corn-and-soybean based meal – and seven diets with bovine meat and bone meal, including or not other ingredients (wheat bran, rice, cottonseed meal, corn gluten meal, sugarcane yeast and brewer yeast). At the 35th day, 24 eggs per treatment were randomly collected, 12 for egg analyses and 12 for yolk and albumen analyses. After isotopic analysis of carbon and nitrogen, the results were submitted to multivariate analysis of variance. The average isotopic pairs of egg, yolk and albumen of all treatments differed from those of the control. The stable isotope technique allowed detection of bovine meat and bone meal in eggs, yolk and albumen, produced by laying hens fed on diets with inclusion of plant ingredients and yeast.